Strategies to Strengthen Mental Health Services in Hospital during Covid-19 - Niken Sasanti Ardi; Dumilah Ayuningtyas (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
Psychiatric disorders that arise due to Covid-19 include anxiety, depression, psychological trauma and the use of drugs to deal with tension caused by the pandemic. A total of 535 respondents (49%) out of 2,364 respondents had thoughts about death. Hospitals must make changes and mitigate, accelerate and adapt faster. This article aims to identify best practice strategies for suicide prevention to improve mental health services in hospitals. This study used queries: "suicide prevention", "covid" and "hospital". The inclusion criteria are English for the issue of 01/01/2020 - 05/10/2020, open access, full-text articles, all types of articles and have keywords. The exclusion criteria were the opposite of the inclusion criteria. The author obtained articles from SpringerLink (13 articles), Pubmed (17 articles), SAGE (4 articles), ProQuest (27 articles), and ScienceDirect (20 articles). Total of 6 articles is excluded because of duplication. 51 articles are excluded because they were not compatible with PICO. Ten articles were excluded because they were a systematic review. The author has 14 articles left for eligibility selection, and all articles are selected for full article review. The recommendation given is to provide comprehensive mental health services in the hospital.